Characterization and development of phenazine-based compounds from Pseudomonas aeruginosa for suppression of Ganoderma boninense - Lee, Kai Wei (2016)
Basal stem rot is caused by Ganoderma boninense and the disease has significantly reduced the productivity of oil palm. Pseudomonas aeruginosa UPMP3 is capable of producing phenazine and phenazine-1-carboxylic acid. It is important to study the potency of these compounds to suppress the fungi, and also to be used as active ingredient in biofungicide formulation. Nanoemulsion is widely used in plant protection, the formulation of phenzine-based compounds in emulsion can be a good substitute to chemicals. The objectives of this project were firstly, to extract and characterize the phenazine-based compounds from P. aeruginosa. Secondly, to formulate nanoemulsion formulation of phenazine-based compounds. Thirdly, to evaluate the suppression efficacy of the formulation on G. boninense in vitro and in vivo. The phenazine compounds were extracted by benzene and characterized by HPLC, FTIR and NMR. The spectra of the characterization were useful to determine the authentic of phenazine-based compounds. Bioassay analysis was run to study the efficacy of the phenazines treatment to suppress G. boninense in vitro and in vivo. The HPLC results showed that phenazine-1-carboxylic acid and phenazine were successfully extracted using benzene and detected at wavelengths 252 and 237 nm at retention time of 51.32 and 52.13 min, respectively. The quantification analysis indicated 11.81 mg of phenazine-1-carboxylic acid and 679.5 mg of phenazine were obtained per one litre of crude extract sample. The FTIR analysis revealed that spectrum had aromatic nitro compound and aromatic rings were indicative the presence of phenazine compound whereas, spectra with carboxylic acid and aromatic rings were indicative of phenazine-1-carboxylic acid. The compounds structure were confirmed by 1H NMR and 13C NMR spectroscopy with the molecular formula C12H8N2 (Phenazine) and C13H8N2O2 (Phenazine-1-carboxylic acid). The bioassay result showed that 5000 ppm crude extract inhibited mycelial growth of G. boninense at 89 %, with LC50 of 2232 ppm whereas purified phenazine treatment gave the best efficacy at 1000 ppm for 100% inhibition, with LC50 of 234 ppm. For nanoemulsion formulation, a phase diagram was constructed with 30% phenazines crude extract as active ingredient through low-energy method. Nanoemulsion F1 with 174.43 nm size was obtained at a ratio 5:5:90 (Tween80: oil carrier: water), and it was found to be stable in terms of polydispersity index (0.6), zeta potential (-16.0 mV) and surface tension (30.88 mN/m), and effective in controlling G. boninense at 70.74% in vitro. In glasshouse trial, Fomulation F1 indicated suppression efficacy identical to positive control (Hexaconazole).The results obtained definitely corroborate to the application of nanoemulsion of phenazine crude extracts as potential candidate for controlling G. boninense. The phenazine nanoemulsion is an innovation alternative to chemical fungicide to control basal stem rot. It shows good potential in the antifungal activity of crude phenazine compounds in nanoemulsion formulation against G. boninense in vitro and suppresses basal stem rot under glasshouse.